1984
DOI: 10.1002/1097-0142(19841101)54:9<1794::aid-cncr2820540907>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Gastric dysplasia. Significance and pathologic criteria

Abstract: In view of uncertainty regarding the criteria and significance of gastric dysplasia as a precancerous lesion, members of the Pathology Panel of the International Study Group on Gastric Cancer (ISGGC) reviewed microslides of 93 gastric lesions showing varying degrees of mucosal abnormality, and reached the following consensus: (1) immature and proliferating gastric epithelium can be divided into two categories: hyperplastic and dysplastic; (2) the term dysplasia, especially of high‐grade type, should be restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
6

Year Published

1986
1986
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(52 citation statements)
references
References 7 publications
0
46
0
6
Order By: Relevance
“…The term "dys" means abnormal and "plasia" means growth; thus, dysplasia is the term for abnormal growth of epithelial cells. Dysplasia is generally defined as unequivocally neoplastic epithelium that may be associated with or develop into invasive adenocarcinoma [9][10][11] . On the other hand, lesions that most European and American pathologists identify as dysplasia are often considered adenocarcinoma in Japan because, according to the Japanese viewpoint, gastric carcinoma is diagnosed based on nuclear and structural atypia, even when invasion is absent.…”
Section: Gastric Intraepithelial Neoplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…The term "dys" means abnormal and "plasia" means growth; thus, dysplasia is the term for abnormal growth of epithelial cells. Dysplasia is generally defined as unequivocally neoplastic epithelium that may be associated with or develop into invasive adenocarcinoma [9][10][11] . On the other hand, lesions that most European and American pathologists identify as dysplasia are often considered adenocarcinoma in Japan because, according to the Japanese viewpoint, gastric carcinoma is diagnosed based on nuclear and structural atypia, even when invasion is absent.…”
Section: Gastric Intraepithelial Neoplasiamentioning
confidence: 99%
“…This confusion has led to several classifications for the terminology between non-neoplastic changes and early invasive cancer [9,11,[14][15][16] . In September 1998, approximately 30 pathologists from 12 countries met in Vienna just before the World Congress of Gastroenterology and reached a consensus on the terminology for gastrointestinal epithelial neoplasia, termed the Vienna classification [17] .…”
Section: Gastric Intraepithelial Neoplasiamentioning
confidence: 99%
“…According to the degree of cellular and structural dysplasia, gastric adenoma is divided into two qualitative grades (low-grade and high-grade dysplasia) or three qualitative grades (mild, moderate and severe dysplasia) (Ming et al, 1984;Tosi et al, 11989: Goldstein and Lewin, 1997). Many authors have investigated the relationship between gastric adenoma and cancer, and showed that the frequency of malignant transformation from adenoma to carcinoma depends on size and histological grade of adenoma (Nakamura et al, 1988;Xuan et al, 1991;Tsujitani et al, 1992).…”
Section: Detection Of Procancer Clones In Human Gastric Adenoma (Otakmentioning
confidence: 99%
“…A hiperplasia foveolar foi caracterizada por alongamento, tortuosidade e hipercelularidade glandular 7 . A definição e classificação das displasias obedeceu aos critérios de Ming 8 , e foram divididas em leve, moderada e intensa.…”
Section: Métodounclassified
“…Na hipótese de formação de adenocarcinoma gástrico induzido por H.pylori, admite-se a seqüência de gastrite crônica atrófica, metaplasia intestinal, displasia 48 . No caso da displasia, importante condição pré-maligna, optou-se pelos critérios de Ming 8 para o seu diagnóstico e classificação, pela universalidade dos mesmos, aliados à sua fácil reprodução.…”
Section: Métodounclassified